A General Synthesis of Fluoroalkylated Alkenes by Palladium‐Catalyzed Heck‐Type Reaction of Fluoroalkyl Bromides1. Issue 4 (2nd December 2014) - Feng, Zhang; Min, Qiao‐Qiao; Zhao, Hai‐Yang; Gu, Ji‐Wei; Zhang, Xingang
Abstract An efficient palladium‐catalyzed Heck‐type reaction of fluoroalkyl halides, including perfluoroalkyl bromides, trifluoromethyl iodides, and difluoroalkyl bromides, has been developed. The reaction proceeds under mild reaction conditions with high efficiency and broad substrate scope, and provides a general and straightforward access to fluoroalkylated alkenes which are of interest in life and material sciences.